2022
DOI: 10.3390/ijerph192316367
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Social Participation and Subjective Well-Being among Older People in the Chinese Culture Context: The Mediating Effect of Reciprocity Beliefs

Abstract: It is demonstrated that the subjective well-being (SWB) of older people greatly relies on their social participation. However, there are few studies on reciprocity beliefs as a mediating mechanism between social participation and SWB. In this study, 297 participants aged 60 and over in Chengdu, Sichuan Province, China, completed a questionnaire of social participation, reciprocity beliefs, and SWB. We used multiple linear regression and mediation analyses to verify the mediating effect of reciprocity beliefs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…Older persons' social participation can, to some extent, provide economic and emotional exchanges with families, as well as foster peace and wellbeing in intergenerational relationships ( 70 ). Social participation is a significant contributor to older persons' mental health ( 71 , 72 ), and it can effectively limit geriatric social isolation while also increasing geriatric social cohesion ( 72 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Older persons' social participation can, to some extent, provide economic and emotional exchanges with families, as well as foster peace and wellbeing in intergenerational relationships ( 70 ). Social participation is a significant contributor to older persons' mental health ( 71 , 72 ), and it can effectively limit geriatric social isolation while also increasing geriatric social cohesion ( 72 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cross-sectional and cohort studies have shown that tooth loss or having few teeth negatively impacts social participation [9][10][11]. Dietary and communication difficulties due to tooth loss reduce social participation and lead to frustration in self-esteem, thus reducing subjective well-being (SWB) [12][13]. A study in Japan reported an independent correlation between the number of teeth and SWB [14].…”
Section: Introductionmentioning
confidence: 99%
“…Collectivism, a unique cultural context in Chinese society, values connections with others and social relationships. In this context, social relationships, such as family and friend-focused network types, highly affect Chinese people’s life satisfaction, especially that of older people, who are deeply influenced by the Chinese traditional culture [60, 61].…”
Section: Introductionmentioning
confidence: 99%